Self-Control dalam Perspektif Al-Junaid - Aqil Rudya Alam; Nady Chiquitta; Fadia Raihan Aqrandista; Dadan Firdaus (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Self-control is an essential aspect of human behavior that enables individuals to regulate their emotions, thoughts, and actions in accordance with moral values and long-term goals. In academic environments, weak self-control may contribute to various forms of deviant behavior, including acts of violence among students. This study aims to examine the concept of self-control from the perspective of Al-Junaid al-Baghdadi’s Sufism, particularly through the concepts of mujahadah and muraqabah, and to analyze their relevance to the phenomenon of violence in higher education institutions. This research employs a qualitative approach using library research and figure study methods. Data were collected from primary sources, including Rasā'il al-Junaid and classical Sufi literature, as well as secondary sources such as books, journal articles, and previous studies related to self-control and Islamic spirituality. The data were analyzed using qualitative content analysis, hermeneutic interpretation, and comparative analysis. The findings reveal that self-control in Al-Junaid’s thought extends beyond behavioral regulation and encompasses the purification of the soul through continuous spiritual struggle and awareness of God's presence. The concepts of mujahadah and muraqabah provide a comprehensive framework for developing internal discipline and moral responsibility. Furthermore, these concepts are highly relevant in preventing aggressive and violent behavior among students because they foster emotional regulation, ethical awareness, and spiritual consciousness. Therefore, Al-Junaid’s Sufi teachings offer a valuable alternative approach to character development within contemporary academic settings.